Work-life balance & burnout among nurses in the inpatient ward of Goeteng Taroenadibrata General Hospital, Purbalingga - Tri Sumarni; Febi Septiani (Riset Informasi Kesehatan, 2026)
Background: Nursing is one of the most stressful professions, and nurses need to have a balance between their work and personal lives (work-life balance). Work-life balance plays an important role in preventing burnout and improving the professional performance of nurses. This study aims to determine the relationship between work-life balance and burnout among nurses. Method: This study is a correlational descriptive study with a cross-sectional approach. The sampling technique used total sampling of 124 nurses. The research instruments were the Work-Life Balance (WLB) Scale questionnaire consisting of 15 questions and the burnout questionnaire using the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) consisting of 22 statements regarding emotional exhaustion, depersonalization, and low personal achievement. Bivariate analysis used the Spearman rank statistical test. Results: Nurses' work-life balance was mostly in the low category (67.7%). The majority of nurses' burnout was in the moderate category (54%). There was a negative relationship between nurses' work-life balance and burnout; the higher the nurses' work-life balance, the lower their burnout (r=0.448, p value=0.001). Conclusion: The need for hospital management to pay attention to all dimensions of work-life balance and factors that contribute to reducing nurse burnout.